A importância da utilização de jogos no ensino da matemática - FERREIRA, Aleido Lima (2022)
The teaching of Mathematics, among other tasks, should provide the student with the ability to solve problems and/or everyday situations, which require a greater content of logical reasoning and other skills that will help him in the search for requests. Therefore, this work portrays a research that had as general objective to present the importance of teaching mathematics through games. For this, a bibliographic research was carried out that made it possible to understand that the use of games in the classroom contributed to the formation of a new concept of teaching, where the student learns in a pleasant way, interacting with the teacher and his colleagues, deconstructing the frightening aspect that often characterizes and stereotypes the Mathematics discipline. In addition, the information acquired throughout this work allowed it to be possible to propose some games capable of contributing to the teacher's methodology to work on the necessary skills in the formation of a habit and concise student in the resolution of problem-situations. It was also possible to create a lesson plan to demonstrate what a class would be like in which the main methodological resource was the game.